In Silico Predictions and In Vivo Results of Drug–Drug Interactions by Ketoconazole and Verapamil on AZD1305, a Combined Ion Channel Blocker and a Sensitive CYP3A4 Substrate. Issue 5 (23rd March 2016) - Johansson, Susanne; Löfberg, Boel; Aunes, Maria; Lunde, Helen; Frison, Lars; Edvardsson, Nils; Cullberg, Marie
Abstract: The objectives were to estimate and compare, in silico and in vivo, the effects of a strong and a moderate CYP3A4 inhibitor on AZD1305 pharmacokinetics. In silico, simulations were performed with the computer software Simcyp, and the predicted outcome was compared with the results observed in healthy male subjects. In silico, the geometric mean plasma exposure of AZD1305 + ketoconazole showed a 7.1‐fold higher AUC and a 4.4‐fold higher Cmax compared with AZD1305 alone. Coadministration with verapamil gave a 1.9‐fold higher AUC and a 1.7‐fold higher Cmax compared with AZD1305 alone. In vivo, the plasma exposure of AZD1305 + ketoconazole showed a 7.7‐fold higher AUC and a 4.8 ‐fold higher Cmax compared with AZD1305 alone. Coadministration with verapamil gave a 2.2‐fold higher AUC and a 2.0‐fold higher Cmax compared with AZD1305 alone. The mean maximum QTcF increase from baseline was 407, 487, and 437 milliseconds for AZD1305, alone and in combination with verapamil or ketoconazole, respectively. Simcyp predicted the effects of ketoconazole and verapamil on the sensitive CYP3A4 substrate AZD1305 pharmacokinetics well. Both the in vivo study and the Simcyp predictions suggest a contraindication for strong CYP3A4 inhibitors and AZD1305 when given in combination.